The development of a real-time feedback system in weightlifting - Ai, K. W.; Bi, Z. Y.; Han, X. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to develop a real-time feedback system (RTFS), which can provide weightlifters some useful information, such as the heights of the bar, video clip and so on, immediately after finishing their attempts under training conditions. A Kinect was used to capture the depth data and RGB video, the methods of the pattern recognition and algorithm were established, and the software was developed to identify the barbell and calculate the 3-D data of barbell COM (Centre of Mass). An experiment was carried out to compare the data from RTFS and that from 3D analysis based on video to check the reliability of RTFS. The results showed that the data of barbell COM obtained by RTFS can describe the movement of barbell sufficiently. This new system can help weightlifters to diagnose their skills and improve their training effectively.